Habitar el Dorado (2017)
"This project becomes a pursuit towards a deep understanding of a territory. Bogotá has stablished as one of the most violent creations of human beings with its territory though this same space has a vast history as a sacred territory. Therefore, the project intents to change the current reality between Bogota and its territory by using the future opportunity of change that brings the metro to the city. Its elevated condition brings a new relation and a new view of the space it occupies and so it is used as a factor of change pretending to create a closer relationship between the habitants and the rivers, the mountains and the ecological habitat".-- Tomado del Formato de Documento de Grado.